A comparison of post-transplantation cyclophosphamide versus antithymocyte-globulin in patients with hematological malignancies undergoing HLA-matched unrelated donor transplantation - Lee, Myung-Won (Medicine (Baltimore), 2020)
Post-transplantation cyclophosphamide (PTCy) and antithymocyte-globulin (ATG) are the most commonly used regimens for prophylaxis of graft-versus-host disease (GVHD). We compared these 2 regimens in human leukocyte antigen (HLA)-matched unrelated donor hematopoietic stem cell transplantation (HSCT) patients with hematological malignancies. We retrospectively analyzed consecutive adult patients with hematological malignancies who underwent HLA-matched unrelated donor-HSCT at Chungnam National University Hospital (Daejeon, South Korea) between January 2013 and January 2019. Patients who received a second transplantation or who had refractory disease were excluded. We included 34 patients (12 and 22 in the PTCy and ATG groups respectively). All graft sources were peripheral blood stem cells. The estimated 20-month overall survival rates were 75.0% for PTCy and 81.6% for ATG patients (P = .792), and the 20-month relapse rates were 41.7% and 34.3% (P = .491), respectively. The cumulative incidences of grade 2 to 4 acute GVHD were 16.7% and 30.6% (P = .551), respectively; the estimated 20-month limited and extensive chronic GVHD rates were 59.1% and 78.8% (P = .718), respectively; and the estimated 20-month extensive chronic GVHD rates were 12.5% and 16.7% (P = .718), respectively. The neutrophil engraftment time was similar in both groups [median (range), 15.0 (12.0–17.0) and 14.0 (12.0–19.0) days, respectively; P = .961]. However, ATG was more expensive than PTCy [median (range), US$4,062 (US$2,215–6,647) for ATG vs US$51.80 (US$43.20–69.20) for PTCy; P < .001]. In conclusion, PTCy and ATG afforded similar clinical outcomes after HLA-matched unrelated donor transplantation but PTCy was less expensive.